The Relationship between Teacher Digital Literacy and the Use of Technology in Learning - Rachel Chan; Marcus Tan; Aditi Verma (Yayasan Pendidikan Islam Daarut Thufulah, 2025)
Background. The integration of technology in education has become increasingly essential for enhancing learning experiences, yet the successful use of technology in teaching relies heavily on teachers’ digital literacy. Digital literacy refers to the ability to use, understand, and evaluate digital tools effectively, and it has been identified as a critical factor influencing the adoption and implementation of technology in the classroom. Purpose. This study investigates the relationship between teachers’ digital literacy and their use of technology in teaching practices. The primary objective is to assess how teachers’ proficiency in digital tools impacts their incorporation of technology into the learning environment. Method. A quantitative research design was employed, using surveys to collect data from 200 teachers across various educational institutions. Descriptive and inferential statistics were used to analyze the data, revealing a positive correlation between digital literacy and the frequency and effectiveness of technology use in the classroom. Results. The findings suggest that teachers with higher levels of digital literacy are more likely to utilize technology in diverse and innovative ways to support student learning. Conclusion. In conclusion, enhancing teachers’ digital literacy is crucial for optimizing the integration of technology in education, thus contributing to more effective and engaging learning experiences.